The combination of virgin olive oils and refined marine oils. Beneficial effects - Østerud, Bjarne; Olvevoll, E. O. (Progress in Nutrition, 2008)
The traditional extraction technique of marine oils from marine products involves heating or steam stripping of the raw material in order to release the lipids. In addition, marine oils are refined. Removal of molecules to improve sensory attributes or safety of the marine oil may destroy potent antioxidants and may as well remove components with potential beneficial effects. Indeed, in several clinical studies performed on marine oils we have observed that this is associated with loss of anti-inflammatory effects probably mediated by removal of beneficial antioxidants. Based on these findings a clinical study with combined cold pressed olive oil with refined seal oil or fish oil was performed. Healthy subjects were given 15 ml/day of the combined oils for 10-14 weeks. These recombined oils appeared to regain properties and behave more like the cold pressed marine oils. The anti-inflammatory effects were seen in reduction of MCP-1 (monocyte chomotactic protein-1), C-reactive protein (CRP), as well as thromboxane B2 and leukotriene B4 in the seal oil combined with olive oil, and reduction in cytokines in the fish oil combined with olive oil. Similar changes were not seen in the marine oils without the presence of olive oil or olive oil alone. In conclusion, cold pressed olive oil has the ability to regain beneficial effects lost during refinement of marine oils.